European Unification and the Dollar Problem - Smithies, A. (Quarterly Journal of Economics, 1950)
Introduction, 159. —I. External economic objectives and unification, 160. — II. Methods of achieving balance with the dollar area, 162. — III. Economic unification and the attainment of external equilibrium, 168. — IV. Conclusion, 181.